Effect of dissolution times on compressive properties and energy absorption of aluminum foam - Nur Surianni Ahamad Suffin,; Anasyida Abu Seman,; Zuhailawati Hussain, (Universiti Kebangsaan Malaysia, 2013)
Aluminum foams were fabricated by sintering dissolution process (SDP) using sodium chloride (NaCl) as space holder. The compositions of space holder, used in this study were 40 and 60 wt. % with different dissolution times; 1, 2 and 3 h. The effect of different dissolution times on compressive behavior and energy absorption of foams were evaluated. The result showed that by increasing space holder and dissolution times, energy absorption capability increases. For aluminum foam contains 60 wt. % NaCl, longer dissolution times resulted in thinner cell wall and cell structure become more unstable which lead to lower plateau region.